If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 5) + -1x = -5x + 15 Reorder the terms: 3(5 + 2x) + -1x = -5x + 15 (5 * 3 + 2x * 3) + -1x = -5x + 15 (15 + 6x) + -1x = -5x + 15 Combine like terms: 6x + -1x = 5x 15 + 5x = -5x + 15 Reorder the terms: 15 + 5x = 15 + -5x Add '-15' to each side of the equation. 15 + -15 + 5x = 15 + -15 + -5x Combine like terms: 15 + -15 = 0 0 + 5x = 15 + -15 + -5x 5x = 15 + -15 + -5x Combine like terms: 15 + -15 = 0 5x = 0 + -5x 5x = -5x Solving 5x = -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 5x + 5x = -5x + 5x Combine like terms: 5x + 5x = 10x 10x = -5x + 5x Combine like terms: -5x + 5x = 0 10x = 0 Divide each side by '10'. x = 0.0 Simplifying x = 0.0
| 4.7=-2.1158(ln*x)+13.669 | | f(x)=(x+2)(x-2)(x-9) | | 3(2x+5)-x=-5+15 | | x/60-x=2/3 | | 20a^2+41a+9=0 | | 3.n/7 | | 49y-126y+81=0 | | -18x-14=-68 | | X=n/7 | | 5x+9+5x=9 | | 2x-13=4x+2 | | 90+(2x-2)+x+5=180 | | 30x+25y=12551 | | 4/4-1/2= | | 10-2x=.5 | | x+(x+10)=15 | | 6/x-3/x=4 | | 3.2x+4.5x+3-2=-2.2x+5x-7 | | 5+x(x-4)=37 | | 4y+9x+3=7+9x | | 2y=y+10 | | 2e^3x+6=32 | | 15/15-12/12 | | 4p-2c-2p+8c= | | sen(5x)=0 | | 3x+2y=8.75 | | I-20=-23 | | 0=30x-16x^2 | | 23/24-11/12 | | 15x(8-5)= | | 6=n/2 | | 9x^2-3x+4=15-x |